Transradial-based thoracic branch endograft repair for thoracic aortic aneurysms experience at a suburban community hospital - Michelle Mendiola Pla, MD, MHSc; Bryan Bennett, DO; Yonjae Kim, MD; Jack R. Chamberlin, MD; Atif Baqai, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
We present two cases where a transradial-based approach was used to implant thoracic branch aortic endografts to repair aortic aneurysms totally percutaneously. Both procedures were performed electively at a 330-bed suburban community hospital. No complications were associated with either procedure with both patients only requiring overnight observation and being discharged home the next day. With careful patient selection, the transradial through-and-through approach for thoracic endovascular aortic repair using the Gore Thoracic Branch Endoprosthesis provides a totally percutaneous option that can be performed feasibly and safely within a community hospital setting.